Responses of orchids to habitat change in Corsica over 27 years - Vogt-Schilb, Hélène; Pradel, Roger; Geniez, Philippe; Hugot, Laetitia; Delage, Alain; Richard, Franck; Schatz, Bertrand (Annals of botany, 2016)
BACKGROUND AND AIMS: Orchids are known to be particularly sensitive to environmental changes due to their narrow ranges of secondary successional habitats. Lack of data at the community level limits our ability to evaluate how traits of different species influence their responses to habitat change. Here, we used a diachronic survey of Mediterranean orchid communities in Corsica to examine this question. METHODS: Using data from two field surveys conducted 27 years apart (1982-84 and 2009-11) at the same 45 sites in Corsica, we evaluated the impact of increase in woody plant cover (WPC) on (i) the richness and composition and (ii) the local extinction/colonization dynamics of orchids. We applied a Bayesian multispecies site-occupancy model to each of the 36 orchid species recorded at these sites to estimate the detection probability of each species, enabling us to account for under-detection in estimating their dynamics. KEY RESULTS: Between 1982 and 2011, WPC changed at 82·3 % of sites (increasing at 75·6 %, decreasing at 6·7 %). Despite marked changes in composition of orchid communities at the local scale, no significant change was detected in species richness at the regional scale. Canopy closure affected the probability of new colonization of sites, but had no significant influence on the probability of local extinction. However, the abundance of shade-intolerant species declined more sharply than that of shade-requiring species. Among orchid species, the detection probability was significantly and positively correlated with population density and plant height. CONCLUSIONS: This study reveals contrasted dynamics of orchid communities between local and regional scales in Corsica. Although high turnover in communities was found at the local scale, regional species richness was maintained despite major land-use changes. Conserving landscape mosaics could provide locally suitable habitats for orchids of different ecologies to maintain diversity at larger spatial scales.
Keywords: detectability; France; ekosystém; conservation; endemism; Ecosystem; biodiverzita; Orchidaceae; Corsica; woody plant cover; Bayesian model; Francie; Mediterranean; orchid communities; Biodiversity